Infection-related hemolysis and susceptibility to Gram-negative bacterial co-infection - Orf, Katharine; Cunnington, Aubrey (Frontiers in Microbiology, 2015)
Increased susceptibility to co-infection with enteric Gram-negative bacteria, particularly non-typhoidal Salmonella, is reported in malaria and Oroya fever (Bartonella bacilliformis infection), and can lead to increased mortality. Accumulating epidemiological evidence indicates a causal association with risk of bacterial co-infection, rather than just co-incidence of common risk factors. Both malaria and Oroya fever are characterised by hemolysis, and observations in humans and animal models suggest that hemolysis causes the susceptibility to bacterial co-infection. Evidence from animal models implicates hemolysis in the impairment of a variety of host defence mechanisms, including macrophage dysfunction, neutrophil dysfunction and impairment of adaptive immune responses. One mechanism supported by evidence from animal models and human data, is the induction of heme oxygenase-1 in bone marrow, which impairs the ability of developing neutrophils to mount a competent oxidative burst. As a result, dysfunctional neutrophils become a new niche for replication of intracellular bacteria. Here we critically appraise and summarize the key evidence for mechanisms which may contribute to these very specific combinations of co-infections, and propose interventions to ameliorate this risk.